The impact of tuberculosis co-infection on virological failure among adults living with HIV in Ethiopia: A systematic review and meta-analysis. (May 2022) - Getaneh, Temesgen; Negesse, Ayenew; Dessie, Getenet; Desta, Melaku
Abstract: Introduction: Tuberculosis (TB) is the most common serious opportunistic infection among people with Human Immunodeficiency Virus (HIV) infection and are considered as the double burden diseases of the world. TB is the leading cause of death among people living with HIV, accounting one in three HIV related deaths. Although TB is responsible for high burden of virological unsuppressed in Ethiopia, there is no national level evidence. Therefore, this systematic review and meta -analysis was aimed at estimating the pooled burden of virological unsuppressed among adults with both HIV-TB and impact of TB on virological failure in Ethiopia. Methods: The finding of this meta -analysis was reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklists. Major data bases PubMed, Scopus, Cochrane Library, Science Direct and Google scholar were searched to access articles. Cochran's Q statistic quantified with inverse variance was computed to check heterogeneity. Funnel plot visualization and Egger's test were fitted to assess publication bias across included studies. Random effects model meta -analysis using STATA version-15 statistical software was used to estimate the pooled effect with respective 95% confidence intervals. Results: A total of 15 primary studies reporting on impact of tuberculosis on virological unsuppressed among adults living with HIV in Ethiopia were eligible for this meta -analysis. Accordingly, the pooled prevalence of virological unsuppressed among adults with both HIV-TB in Ethiopia was 39.09% (95% CI: 29.04, 49.15). In addition, the odds of virological unsuppressed among adults with both HIV-TB was 2.46 times higher when compared with adults living with HIV infection alone (OR = 2.46, 95% CI: 1.74, 3.46). Conclusion: The present systematic review and meta -analysis evidenced that the pooled prevalence of virological unsuppressed among adults with both HIV-TB was much higher than virological unsuppressed among adults living with HIV alone. Moreover, the odds of virological failure among adults with both HIV-TB was significantly higher when compared with among only HIV infection in Ethiopia. Therefore, strengthening TB prevention interventions, early identification and managing the case and prioritizing viral load monitoring and adherence support among adults living with HIV are recommended.